2(x-5)+x=4x-1+2x

Simple and best practice solution for 2(x-5)+x=4x-1+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-5)+x=4x-1+2x equation:


Simplifying
2(x + -5) + x = 4x + -1 + 2x

Reorder the terms:
2(-5 + x) + x = 4x + -1 + 2x
(-5 * 2 + x * 2) + x = 4x + -1 + 2x
(-10 + 2x) + x = 4x + -1 + 2x

Combine like terms: 2x + x = 3x
-10 + 3x = 4x + -1 + 2x

Reorder the terms:
-10 + 3x = -1 + 4x + 2x

Combine like terms: 4x + 2x = 6x
-10 + 3x = -1 + 6x

Solving
-10 + 3x = -1 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-10 + 3x + -6x = -1 + 6x + -6x

Combine like terms: 3x + -6x = -3x
-10 + -3x = -1 + 6x + -6x

Combine like terms: 6x + -6x = 0
-10 + -3x = -1 + 0
-10 + -3x = -1

Add '10' to each side of the equation.
-10 + 10 + -3x = -1 + 10

Combine like terms: -10 + 10 = 0
0 + -3x = -1 + 10
-3x = -1 + 10

Combine like terms: -1 + 10 = 9
-3x = 9

Divide each side by '-3'.
x = -3

Simplifying
x = -3

See similar equations:

| 3x-5(x-5)=7+2x+4 | | 6x-3=-11 | | m=10-x | | 8.1+1.8h=-7.2 | | (M-7)(m-3)=0 | | 45-61=4x-2x | | 1.5x+0.5=12 | | 3x-4x=-22 | | bx-ay+2z=-19 | | 72y+4.7=62.3 | | 6x^2-3=x^3-169 | | 4a+5b+c=6 | | -x-3(2)=-11 | | 9r^2+2r-24=0 | | 30x=540 | | 5-4k=12x+7 | | x^2+7x+20=3x+17 | | -9y+3x=-9 | | 95m-2=80a+3 | | 6=10(k+.6) | | 2x+22+122=14x | | m/(-3)=-5-18 | | 6x-5+8x-2x-3=9w-24 | | 0.40x+0.25(140)=0.20(113) | | 5t-2=3t-8+8t | | 3x(5)+3=18 | | m^2+7m+5=0 | | 10t-4t=-11 | | 2x+19=8x-41 | | 12p+3q-5p+8q= | | 3a-b+c=10 | | 16x+8=32x+16 |

Equations solver categories